Global AIDS Funding and the Re-Emergence of AIDS 'Exceptionalism' - Lisa Forman (Social Medicine Publication Group, 2011)
Recent years have seen the re-emergence of charges of AIDS exceptionalism in response to 'revolutionary' increases in global funding for health that have coalesced around HIV/AIDS treatment. These increases are argued to illustrate that AIDS demands an exceptional and exaggerated portion of global resources to the detriment of other health needs and the strengthening of health systems. I argue in contrast that AIDS 'exceptionalism' in funding represents a welcome departure from a long-standing norm that tolerates grossly insufficient domestic and global allocations to health. In this light, AIDS 'exceptionalism' while a political anomaly, has acted as a corrective to exclusionary and inequitable HIV/AIDS policies.